Helping Rabbits Cope with Veterinary Acts and Vaccine-Related Stress: The Effects of the Rabbit Appeasing Pheromone (RAP) - Pietro Asproni; Elisa Codecasa; Miriam Marcet-Rius; Juliane Demellier; Estelle Descout; Marine Verbaere; Orane Vinck; Patrick Pageat; Alessandro Cozzi (Animals)
Rabbits are subjected to challenges that induce stress and require them to continuously adapt. Veterinary procedures represent an important source of stress. In other pets, pheromone use was shown to help patients better cope with these procedures. This study aimed to evaluate whether continuous exposure to the rabbit appeasing pheromone (RAP) could help rabbits cope with the stress induced by routine clinical consultations and vaccinations. Twenty-four 5-week-old rabbits were housed in two identical rooms for 43 days, one in which the rabbits underwent continuous RAP treatment and one with the placebo. The rabbits were vaccinated 8 days afterwards, and their behaviour was evaluated using visual analogic scales (VASs) and videos. The rabbits were also examined seven times, on a weekly basis, using VASs to assess their behaviour. The video analysis showed that the RAP-treated rabbits were less inhibited (p = 0.03) and more in contact with the surgeon (p = 0.039) during vaccinations, while the non-treated rabbits kept their ears in the middle/flattened position (p = 0.003). The RAP-treated rabbits were also less agitated (VAS analysis, p = 0.02). During the consultations, a treatment × day effect was observed in favour of the RAP group for the rabbit state and rabbit reactivity VAS analysis (p < 0.0001). These findings seem to suggest that continuous RAP exposure could be a promising tool for helping rabbits cope with veterinary procedures.